Application of the movement disorder society prodromal Parkinson's disease research criteria in 2 independent prospective cohorts. Issue 7 (16th May 2017) - Pilotto, Andrea; Heinzel, Sebastian; Suenkel, Ulrike; Lerche, Stefanie; Brockmann, Kathrin; Roeben, Benjamin; Schaeffer, Eva; Wurster, Isabel; Yilmaz, Rezzak; Liepelt‐Scarfone, Inga; von Thaler, Anna‐Katharina; Metzger, Florian G.; et al.
ABSTRACT: Background: The research criteria for prodromal PD of the MDS propose a new approach for the assessment of the individual probability of prodromal PD. These criteria require a testing of their reliability in different prospective cohorts. Objectives: The objective was to evaluate the MDS prodromal PD criteria in 2 independent prospective studies. Methods: Prodromal PD probabilities of the Tübingen Evaluation of Risk Factors for Early Detection of Neurodegeneration cohort (TREND study, n = 650, recruited by the presence of probable rapid eye movement sleep behavior disorder, depression, and/or hyposmia or none of these at baseline and 2‐, 4‐, and 6‐year follow‐up) and the population‐based Prospective Evaluation of Risk Factors for Idiopathic Parkinson's Syndrome cohort (PRIPS Tübingen subsample; n = 715, baseline and 3‐ and 5‐year follow‐up) were calculated. Baseline posttest probabilities, time to PD diagnosis, marker constellations, and longitudinal changes of prodromal PD probabilities were analyzed. Results: Incident PD cases (TREND, n = 10; PRIPS = 7) showed significantly higher likelihood ratios of risk and prodromal markers at baseline when compared with nonconverters. Only 2 of 17 incident PD cases met the criteria for probable prodromal PD (ie, posttest probability > 80%) and 5 had possible prodromal PD (ie, > 50%) 1.4 to 3.8 years before diagnosis. The criteria showed high specificity and negative predictive values (>98%), but low sensitivity (TREND, 30%; PRIPS, 14%) and positive predictive values (TREND, 19%, PRIPS, 50%). The individual risk for prodromal PD in incident PD cases showed an inverse correlation with the time to conversion (Spearman rho = .80, P = .006) and unlike in nonconverters, increased during follow‐up. Conclusion: The MDS prodromal criteria provide a practical framework for the calculation of prodromal PD risk. Although specificity of the criteria is high, most patients will not meet the criteria before diagnosis unless testing is thoroughly performed with numerous and highly specific markers objectively assessed. © 2017 International Parkinson and Movement Disorder Society